Janusza Stannego przygoda z plakatem filmowym - Stanny, Katarzyna (Załącznik Kulturoznawczy, 2024)
Professor Janusz Stanny, a legend and master of Polish illustration, was also a poster artist. His creative path might have taken a different course had it not been for the premises, which were then necessary to paint large format posters. He studied at the State Printing High School, where he designed his first posters while working for the military press, then he became a student at the Graphics Department of the Academy of Fine Arts in Warsaw. He made his dream come true and took up studies in Henryk Tomaszewski’s poster studio. At that time, he started cooperation with the magazines “Szpilki” and “Dookoła Świata”, as well as with the publishing houses Iskry and Czytelnik. He actively participates in the 5th Festival of Youth and Students, sketching foreign guests. It was during his studies that Janusz Stanny’s first film posters were created, commissioned by Centrala Wynajmu Filmów. The posters are: Dark River, Irena Go Home!, The Ox of Kulm and The Partisans. After graduating from the Poster Studio, he designs covers. Short, intelligent thinking and a simple graphic form are the important elements taken from Tomaszewski’s studies, which Stanny transfers to the area of a graphic form smaller than a poster, which is the cover. At that time, he buys a tiny, charming studio in the Old Town at Świętojańska street, where, also due to the limited space, he devotes himself to work on illustrations and author’s books, and also accepts the proposal to replace Jan Marcin Szancer at the RUCH publishing house. In the 1970s, he exchanged a small art studio for a much larger one, enabling him to work freely on larger formats, then he took over the Book and Illustration Studio at the Faculty of Graphic Arts, which he would lead until 2004. Studies in Henryk Tomaszewski’s Poster Studio had a huge impact on Stanny’s thinking about illustration, both in the area of his own work, as well as in academic teaching. For 28 years he headed the Illustration Studio at the Faculty of Graphic Arts of the Academy of Fine Arts in Warsaw, remaining in the circle of his master, Professor Henryk Tomaszewski and other poster artists: Julian Pałka, Maciej Urbaniec, Waldemar Świerzy and Rosław Szaybo. Both academic education and Stanny’s work would not be what they were had it not been for his studies in Tomaszewski’s studio and his first steps in the field of film poster there.